Phytochemical Screening Analysis and Determination of Total Flavonoids and Total Phenolics Content of Ethanol Extract of Sungkai Leaf (Penorema canescens Jack) from Samarinda City - Muhammad Ma'ruf; Moch. Saiful Bachri; Laela Hayu Nurani (Program Studi Farmasi Universitas Mandala Waluya, 2023)
Sungkai is a plant that contains compounds such as flavonoids, tannins, phenolics, saponins, steroids, and terpenoids, which have the potential to develop native Indonesian herbal medicines to treat the prevention and treatment of various diseases. This research aimed to analyze phytochemical screening and the total flavonoid and phenolic content in sungkai leaves originating from Samarinda City. This research method was carried out by extracting sungkai leaves with 96% ethanol and evaporating them with a vacuum rotary evaporator. Sungkai leaf extract was analyzed for phytochemical screening using the tube method with color testing from various reagents and total phenolic and flavonoid content testing using the colorimetric method using a UV-Vis spectrophotometer. The results of the phytochemical screening showed that the ethanol extract of sungkai leaves from Samarinda City was positive for containing flavonoids, saponins, alkaloids, phenolics, and steroids. The results of determining the flavonoid and phenolic content of sungkai leaf ethanol extract were 18,210 ± 0.271 mg QE/g sample and 33,666 ± 1.052 mg GAE/g sample.